Niger : Towards Water Resource Management - World Bank (Washington, DC, 2013)
The study reviews Niger's water resources, and planning process, through its short- and medium-term water investment program, and priorities in the water supply, and sanitation sector. Critical challenges are examined for improving its complex water resources management to support economic growth, given its landlocked situation, with diffuse, and mostly rural population, and immense, untapped fossil aquifer supplies. Despite multiple surface water basins, very little precipitation occur, thus the government has recently undertaken a ten-year process of preparing a water resource management investment strategy, one that requires financial resources currently unavailable. Information and data management, institutional arrangements, and the legal, and regulatory framework is analyzed to achieve a feasible master plan, and strengthen implications for the water sub-sectors. Recommendations suggest the development of financing mechanisms, consistent with sustainable management of water resources, in line with strengthening water data collection, and information systems.